The state of realization and investment support of the Energy strategy of Ukraine - Kulyk М.M. (General Energy Institute of the National Academy of Sciences of Ukraine, 2012)
The comparison of the actual indicators of Ukraine’s energetic economic development in 2005-2011 with the corresponding basic forecasted indicators of the acting Energy strategy (ES) of Ukraine (gross domestic product (GDP), primary fuel-energy resources (FER), electric power, natural gas, and GDP power consumption) is performed. It is established that the indicated actual indicators in 2006-2008 were close or better than those of the optimistic scenario of ES. The financial economic crisis in 2008 and subsequent years broke this tendency to the side of their significant deterioration in 2009. However, the volumes of GDP, electric power consumption, and primary FER fell on the pessimistic development trajectory forecasted by the acting Energy strategy already in 2011 (their divergence with actual data is 1.5-2.5 %). This demonstrates a sufficiently high accuracy and the reliability of the forecasting executed at the development of the acting Energy strategy.It is shown that the conditions and the requirements concerning the backing of the necessary sizes of financing of the processes of innovation and development of the enterprises of the electric power complex (EPC) in 2006-2010 become essentially worse as compared with those in the period 2001-2005. The situation formed in the investment of Ukraine’s EPC requires that the capital investment to its development be realized not only at the expense of enterprises-producers, but also from an additional powerful source, namely from State’s fund for development of EPC (Fund).It is expedient to ensure the replenishment of the Fund at the expense of the following sources: target electric rate charges; state’s preferential credits; state’s investments to the development of EPC; and state’s part of incomes from the activity of the enterprises of EPC. The target electric rate charges are the most reliable and powerful source.To ensure the size of investments from the Fund, which exceed or are equal to 50% of the required ones, it is sufficient to set the target rate charges to be 17.3-20 % (the period till 2020). In the subsequent periods during the formation of the processes of steady development in Ukraine’s economy, the target rate charge can be decreased down to 3.8 %. The mean target electric rate charge for the whole period till 2030 is equal to 13 %.The indicated values of target charges are quite suitable for country’s economy and social sphere. Their introduction will give possibility for power companies to perform a technical reequipment of the branches of Ukraine’s EPC aimed at the attainment of the technical and economic indicators corresponding to those of the power systems of EC.